Living supramolecular polymerization - Mukhopadhyay, Rahul Dev; Ajayaghosh, Ayyappanpillai (Science (American Association for the Advancement of Science), 2015)
Greater control is achieved over the chain growth and properties of dynamic materials Most polymers that we encounter, like those used in grocery bags and soda bottles, are formed from small molecules (monomers) held together by strong covalent bonds. In supramolecular polymerization, monomers bond through weaker reversible interactions, such as hydrogen bonds (H-bonds). Supramolecular polymerization usually proceeds through step-growth mechanisms ( 1 ), where both ends of each monomer are reactive and many smaller oligomers form before long polymers appear. To overcome this problem, a method developed for covalent polymers known as living polymerization has been adopted for supramolecular polymers to achieve better control and uniformity of chain growth and dispersity.